Peroxisome Proliferator–Activated Receptor γ Regulates Chronic Alcohol-Induced Alveolar Macrophage Dysfunction - Yeligar, Samantha M. (Am J Respir Cell Mol Biol, 2016)
Peroxisome proliferator–activated receptor (PPAR) γ is critical for alveolar macrophage (AM) function. Chronic alcohol abuse causes AM phagocytic dysfunction and susceptibility to respiratory infections by stimulating nicotinamide adenine dinucleotide oxidases (Nox), transforming growth factor-β(1), and oxidative stress in the AM. Because PPARγ inhibits Nox expression, we hypothesized that alcohol reduces PPARγ, stimulating AM dysfunction. AMs were examined from: (1) patients with alcoholism or control patients; (2) a mouse model of chronic ethanol consumption; (3) PPARγ knockout mice; or (4) MH-S cells exposed to ethanol in vitro. Alcohol reduced AM PPARγ levels and increased Nox1, -2, and -4, transforming growth factor-β(1), oxidative stress, and phagocytic dysfunction. Genetic loss of PPARγ recapitulated, whereas stimulating PPARγ activity attenuated alcohol-mediated alterations in gene expression and phagocytic function, supporting the importance of PPARγ in alcohol-induced AM derangements. Similarly, PPARγ activation in vivo reduced alcohol-mediated impairments in lung bacterial clearance. Alcohol increased levels of microRNA-130a/-301a, which bind to the PPARγ 3′ untranslated region to reduce PPARγ expression. MicroRNA-130a/-301a inhibition attenuated alcohol-mediated PPARγ reductions and derangements in AM gene expression and function. Alcohol-induced Toll-like receptor 4 endocytosis was reversed by PPARγ activation. These findings demonstrate that targeting PPARγ provides a novel therapeutic approach for mitigating alcohol-induced AM derangements and susceptibility to lung infection.